Brass bands and the beni phenomenon in urban east Africa - Martin, Stephen H. (International Library of African Music, 2017)
With the advent of the German and British colonial administrations to the coast of East Africa in the late 1800s came also the complements of military machinery and military music. This paper will investigate the impact of the music of the European military brass band on the coastal and inland areas of Tanganyika as manifested in the development, florescence and demise of beni ngoma.
Keywords: African Music